Strategies to manage electronic waste approaches: an overview in Malaysia - Al-Rahmi, Waleed; Alias, Norma; Dahawi, Abdullah Aysh; Yahaya, Noraffandy; Saleh, Muneer; Al-Maatouk, Qusay (International Journal of Engineering and Technology, 2018)
The issue of e-waste is becoming an increasingly threatening problem as it contains many toxic materials that can severely harm both human beings and the environment. This problem is expected to worsen if not serious efforts are taken to manage this e-waste. The current paper introduced quantity of e-waste generated and their negative impact on both environment and human beings in some countries including Ma-laysia. It also presents the managerial efforts taken in this regard to deal with the e-waste. The current study is an effort to decrease the dan-ger and solve e-waste problems. For that, it utilized different tools such as LCA, MFA, MCA and EPR. Over and above all of these, no matter how well the policies are introduced and implemented beneï¬ts will only arise provided end users are prepared to accept introduced policies and adhere to them.